P4_2 The Destruction of the DS-1 - Howard-Clark, Simon; Graham, Holly; Sainty, William; Kneeshaw, Sam (Physics Special Topics, 2017)
In this paper we aim to investigate the demise of the DS-1 (Death Star I) Orbital Battle Station over the planet Yavin in the film “Star Wars: A New Hope” and propose any effects the explosion would have on Yavin IV. Kepler’s 3rd law and Pythagoras Theorem are used to find the distance between Yavin IV and the Death Star, showing at the time of the explosion the Death Star is 1.17 × 1011 m away from Yavin IV. The flux density (irradiance) at the surface of Yavin IV is also calculated giving a value of 1.17 × 109 W m−2 , which we believe would be more than enough radiation to cause mass extinctions on Yavin IV, even at this extreme distance.